The Performance Gain of Cognitive Radio in Adaptive Modulation Scheme - Foukalas, Fotis (Scientific Research Publishing, 2010)
Cognitive radio is considered as one of the main enablers for provisioning dynamic and flexible spectrum/channel allocation in wireless communications. The reliable data transmission over cognitive radio should employ modulation, coding etc. and thus the performance of such a new communication system should be realized. In this paper, we provide the performance analysis of adaptive modulation over a cognitive radio system in order to study the potential gain of cognitive radios in terms of spectral efficiency. The results obtained show that the performance gain of cognitive radio in adaptive modulation is remarkable.
Keywords: Cognitive Radio; Adaptive Modulation; Performance Gain